A defensin-like antimicrobial peptide from the manila clam Ruditapes philippinarum: Investigation of the antibacterial activities and mode of action. Issue 80 (September 2018) - Yang, Dinglong; Zhang, Qianqian; Wang, Qing; Chen, Lizhu; Liu, Yongliang; Cong, Ming; Wu, Huifeng; Li, Fei; Ji, Chenglong; Zhao, Jianmin
Abstract: Defensins are small cysteine-rich cationic proteins that are ubiquitously present in both vertebrates and invertebrates and constitute the front line of host innate immunity. In the present study, a defensin-like antimicrobial peptide (designed as RpdefB) was identified and characterized from the manila clam Ruditapes philippinarum . The open reading frame of RpdefB encoded a 70-amino acid polypeptide with a calculated molecular mass of 7.5 kDa and isoelectric point of 8.16. Multiple alignments and phylogenetic analysis strongly suggested that RpdefB was a new member of the defensin family. In non-stimulated clams, RpdefB transcripts were constitutively expressed in all five tested tissues, especially in the hepatopancreas. After Vibrio anguillarum challenge, expression of RpdefB mRNA in hemocytes was significantly up-regulated at 6 h, 12 h and 72 h. The synthetic peptide RpdefB showed high antibacterial activity against the Gram-negative bacterium Vibrio splendidus . Moreover, membrane integrity analysis revealed that RpdefB increased the membrane permeability of Escherichia coli and then resulted in cell death. Overall, our results suggested that RpdefB played an important role in the elimination of invading bacterium, perhaps through membrane-disruptive activity. Highlights: A defensin-like antimicrobial peptide was identified from the manila clam Ruditapes philippinarum. RpdefB showed anti-bacterial activity against Gram-positive and Gram-negative bacteria. RpdefB eliminated invading bacteria perhaps through membrane-disruptive activity.